2004
DOI: 10.1016/j.ymthe.2003.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis and Lentiviral Transduction of Fetal Monkey Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: We explored the transduction kinetics of HIV-1-derived lentiviral vectors containing the CMV, EF1alpha, or PGK promoter expressing EGFP in fetal rhesus monkey bone marrow-derived mesenchymal stem cells (rhMSC). Studies included the effects of transduction (MOI 0-100) on growth, cell cycle, and differentiation toward an osteogenic lineage. Flow cytometric analysis indicated an approximate 8- to 10-fold greater quantity of EGFP-expressing rhMSC when cells were transduced with the CMV or EF1alpha promoter compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 47 publications
1
41
0
3
Order By: Relevance
“…Remarkable progress has been made in the recent past in using retroviral or lentiviral vectors to deliver therapeutic genes into MSCs (Zhang et al, 2002;Lee et al, 2004;Reiser et al, 2005;Barzilay et al, 2009;Jacome et al, 2009) or in deriving iPS cells from adult somatic cells (Welstead et al, 2008;Sommer et al, 2009) Townes, 2008). However, both retroviral and lentiviral vectors undergo random integration into host chromosomal DNA, and there is persistent risk for insertional mutagenesis (Cockrell and Kafri, 2007;Nair, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkable progress has been made in the recent past in using retroviral or lentiviral vectors to deliver therapeutic genes into MSCs (Zhang et al, 2002;Lee et al, 2004;Reiser et al, 2005;Barzilay et al, 2009;Jacome et al, 2009) or in deriving iPS cells from adult somatic cells (Welstead et al, 2008;Sommer et al, 2009) Townes, 2008). However, both retroviral and lentiviral vectors undergo random integration into host chromosomal DNA, and there is persistent risk for insertional mutagenesis (Cockrell and Kafri, 2007;Nair, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A candidate for this minor population could be the still elusive osteoprogenitor cell that maintains the potential to proliferate and to differentiate (42). Progenitors are indubitably present in primary osteoblast cultures, which undergo several population doublings before senescence (43), and previous work has shown that LVs transfer genes in bona fide stem cells (44), including bone precursors (45). Although unidentified, the osteoprogenitor targeted by MET likely belong to the family of mesenchymal stem cells, which are also the precursors of rhabdomyosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…26 We are aware that other constitutive promoters like elongation factor 1 would allow an even better expression, but no direct comparisons have been reported in literature yet. 27,28 Analysis and comparison of the BLI and FLI performances in vivo were possible, since fusion of the reporters ensured equimolar expression in cells. Our results showed that the limit of detection using BLI is approximately 1 Â 10 3 hMSCs in the brain cortex using a dose of 25 mM/kg of D-Luc.…”
Section: Discussionmentioning
confidence: 99%